2023
DOI: 10.3390/cancers15061634
|View full text |Cite
|
Sign up to set email alerts
|

More than Meets the Eye: Integration of Radiomics with Transcriptomics for Reconstructing the Tumor Microenvironment and Predicting Response to Therapy

Abstract: For over a decade, large cancer-related datasets (big data) have continuously been produced and made publicly available to the scientific community [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Transcriptomics, genomics, proteomics, metabolomics, and glycomics are some of the '-omics' data that are converging to identify critical bioindicators and biomarkers that can be used to train models. These can be further combined with radiomics to identify populations that could be radiosensitive [186][187][188]. For example, Zhang et al combined gene expression, DNA methylation, and clinical data to identify eight radiosensitivityrelated genes (AR, WBP1, AKR1E2, FANCG, NR2C2AP, CXCR4, SYNE4, and WFDC2) [189], while Liu et al identified 12 genes (BEST2, TMPRSS15, FGF19, ALP1, KCNB2, CLDN6, IL17REL, RORB, DDX25, TDRD9, CELF3, and FABP7) that can aid in identifying population responses in head and neck cancer patients [190].…”
Section: Challenges and Opportunities For Cancer Radiosensitivity Bio...mentioning
confidence: 99%
“…Transcriptomics, genomics, proteomics, metabolomics, and glycomics are some of the '-omics' data that are converging to identify critical bioindicators and biomarkers that can be used to train models. These can be further combined with radiomics to identify populations that could be radiosensitive [186][187][188]. For example, Zhang et al combined gene expression, DNA methylation, and clinical data to identify eight radiosensitivityrelated genes (AR, WBP1, AKR1E2, FANCG, NR2C2AP, CXCR4, SYNE4, and WFDC2) [189], while Liu et al identified 12 genes (BEST2, TMPRSS15, FGF19, ALP1, KCNB2, CLDN6, IL17REL, RORB, DDX25, TDRD9, CELF3, and FABP7) that can aid in identifying population responses in head and neck cancer patients [190].…”
Section: Challenges and Opportunities For Cancer Radiosensitivity Bio...mentioning
confidence: 99%
“…This approach enables the conversion of qualitative information, based on medical doctors' experience, into objective information. In other words, by analyzing quantitative features, radiomics aims to uncover valuable information that may not be discernible through traditional visual inspection alone [32]. The radiomics features can be extracted starting from the original images or after performing the wavelet filter, i.e., the images are first decomposed according by the SWT and then the features are calculated on each part [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%